THE RELATIONSHIP BETWEEN WORKPLACE FRIENDSHIP AND EMPLOYEE ENGAGEMENT: THE MEDIATING EFFECT OF PERCEIVED ORGANIZATIONAL JUSTICE - Chueh-An Chen (PEOPLE: International Journal of Social Sciences, 2026)
This study, grounded in Social Exchange Theory (Blau, 1964), aims to examine the relationships among workplace friendship, perceived organizational justice, and employee engagement, including work engagement and organizational engagement, as well as the mediating role of perceived organizational justice. A questionnaire survey method was employed, and data were collected from 53 valid responses of full-time employees. The results indicate that workplace friendship has a significant positive effect on both work engagement and organizational engagement. In addition, perceived organizational justice positively predicts both forms of engagement. Furthermore, perceived organizational justice plays a mediating role in the relationship between workplace friendship and organizational engagement. Overall, the findings support the applicability of Social Exchange Theory in workplace interpersonal contexts and suggest that fostering positive workplace relationships and enhancing perceptions of fairness can effectively improve employee engagement. These results provide practical implications for human resource management and employee relations practices.